Supervision Management and Evaluation of the Principal of School at Madrasah Aliyah Al-Musdariyah Cimahi - Ai Deudeu Maria Dewi; Nurmalasari Nurmalasari; Mohamad Erihadiana (EDUTEC : Journal of Education And Technology, 2023)
The purpose of this study is to assess the management of supervision and evaluation of the Principal at MA Al Musdariya Cimahi. This study's methodology employs descriptive qualitative analysis to examine the management, supervision, and evaluation of school principals. Interview techniques, documentation, and observations that were directly derived from primary data and secondary data were employed in technical data analysis.The following are the outcomes of the application of supervision; First, the Individual technique, which entails (a) visiting classes, (b) watching classes, and (c) having private dialogues. The second category of group techniques consists of discussions and teacher meetings. Evaluation At MA Al Musdariyah, supervision management is carried out by the principal in his capacity as an evaluator by reviewing all school administrative arrangements made by all instructors to ensure that supervision and evaluation function as they should.